Viabilidade econômica da cogeração de energia a partir do biogás: um estudo de caso no aterro sanitário de Toledo, Paraná - Jacobowski, Marcelo (2018)
The present study aims to analyze the economic viability of electric power generation from the biogas production in the sanitary landfill of the municipality of Toledo PR. Currently, the country has been experiencing difficulties in the energy efficiency sector, as the largest portion of electricity generated comes from hydroelectric power plants, which in turn are suffering from low levels of their reservoirs provided by climatic instabilities. Considering the difficulty that the country is experiencing with its energy matrix, the present study becomes relevant for exploring an alternative for the production of local electric energy. In view of these facts, the purpose of the work is to identify the biogas generation capacity for the subsequent production of electric energy and to verify the economic viability of this activity. The study will perform an exploratory and descriptive research using primary data with research questionnaires, semi-structured interviews and direct analysis, as well as secondary data, using documentary surveys, bibliographic research, site search and specialized journals.